2016
DOI: 10.1155/2016/7589068
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of 4-Chloro-2-nitrophenol-Degrading Bacteria in a Waste Water Sample

Abstract: Eighteen bacterial strains, isolated from a waste water sample collected from a chemically contaminated site, Patancheru (17°32′N 78°16′E/17.53°N 78.27°E), India, were able to decolorize 4-chloro-2-nitrophenol (4C2NP) in the presence of an additional carbon source. These eighteen 4C2NP-decolorizing strains have been identified as members of four different genera, includingBacillus,Paenibacillus,Pseudomonas, andLeuconostocbased on the 16S rRNA gene sequencing and phylogenetic analysis. Most of the bacteria (10)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…Previous studies on AS have shown bacterial families other than Alcaligenaceae and Pseudomonadaceae , to be dominant in aeration tanks of AS treatment [19, 32]. Although Alcaligenaceae and Pseudomonadaceae contain the genera Alcaligenes and Pseudomonas which are known to degrade a range of xenobiotics [35, 36, 37, 38], their dominance in aeration tanks is not in accordance with some earlier studies [12, 13, 14, 19, 32, 33]. In our previous culture-dependent study, we showed the presence of highly drug-resistant bacterial strains belonging to genera Pseudomonas , Alcaligenes , Advenella , Bordetella , and Castellaniella .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on AS have shown bacterial families other than Alcaligenaceae and Pseudomonadaceae , to be dominant in aeration tanks of AS treatment [19, 32]. Although Alcaligenaceae and Pseudomonadaceae contain the genera Alcaligenes and Pseudomonas which are known to degrade a range of xenobiotics [35, 36, 37, 38], their dominance in aeration tanks is not in accordance with some earlier studies [12, 13, 14, 19, 32, 33]. In our previous culture-dependent study, we showed the presence of highly drug-resistant bacterial strains belonging to genera Pseudomonas , Alcaligenes , Advenella , Bordetella , and Castellaniella .…”
Section: Resultsmentioning
confidence: 99%
“…Low bacterial diversity in PETL is likely to be one of the factors behind this. In environments exposed over longer times to chemical stressors, such as in the highly contaminated environments in Patancheru, it is possible that the microbial diversity could be partly restored, either because bacteria gain the ability to tolerate or even utilize the contaminants, or because sensitive species replace tolerant ones, or a combination of both processes [6, 38, 42]. …”
Section: Resultsmentioning
confidence: 99%
“…Recently, ten bacterial strains belonging to Bacillus isolated from a wastewater sample showed decolorization of 4-chloro-2-nitrophenol in the presence of glucose. One of a bacterium, identified as Bacillus aryabhattai strain PC-7 decolorized 4-chloro-2-nitrophenol up to a concentration of 2.0 mM and transformed it into 5-chloro-2-methylbenzoxazole (Arora et al, 2016 ).…”
Section: Role Of Bacillus Species In Biodegradatiomentioning
confidence: 99%
“…Bacilli are considered as potential bioremediator agents, which are capable of degrading several toxic substances (Arora et al, 2016 ; Singh and Singh, 2016 ; Xiao et al, 2017 ). Earlier studies have also been reported degradation of various xenobiotic compounds and heavy metals by the members of genus Bacillus (Birolli et al, 2016 ; Upadhyay et al, 2017 ; Arora et al, 2018 ; Díez-Méndez et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Large volumes of pharmaceutical sludge are produced from pharmaceutical wastewater plants, and they pose containing high environmental risk because of the hazardous and refractory organic pollutants contained in the sludge [ 1 , 2 ]. In particular, pharmaceutical sludge contains relatively high levels of soluble organics, heavy metals, and recalcitrant antibiotics [ 3 , 4 ], such as benzylpenicillin [ 5 ], aureomycin [ 6 ], and berberine hydrochloride [ 7 ].…”
Section: Introductionmentioning
confidence: 99%